Imbalance in subregional connectivity of the right temporoparietal junction in major depression. Issue 8 (19th April 2016) - Poeppl, Timm B.; Müller, Veronika I.; Hoffstaedter, Felix; Bzdok, Danilo; Laird, Angela R.; Fox, Peter T.; Langguth, Berthold; Rupprecht, Rainer; Sorg, Christian; Riedl, Valentin; Goya‐Maldonado, Roberto; Gruber, Oliver; et al.
Abstract: Major depressive disorder (MDD) involves impairment in cognitive and interpersonal functioning. The right temporoparietal junction (RTPJ) is a key brain region subserving cognitive‐attentional and social processes. Yet, findings on the involvement of the RTPJ in the pathophysiology of MDD have so far been controversial. Recent connectivity‐based parcellation data revealed a topofunctional dualism within the RTPJ, linking its anterior and posterior part (aRTPJ/pRTPJ) to antagonistic brain networks for attentional and social processing, respectively. Comparing functional resting‐state connectivity of the aRTPJ and pRTPJ in 72 MDD patients and 76 well‐matched healthy controls, we found a seed (aRTPJ/pRTPJ) × diagnosis (MDD/controls) interaction in functional connectivity for eight regions. Employing meta‐data from a large‐scale neuroimaging database, functional characterization of these regions exhibiting differentially altered connectivity with the aRTPJ/pRTPJ revealed associations with cognitive (dorsolateral prefrontal cortex, parahippocampus) and behavioral (posterior medial frontal cortex) control, visuospatial processing (dorsal visual cortex), reward (subgenual anterior cingulate cortex, medial orbitofrontal cortex, posterior cingulate cortex), as well as memory retrieval and social cognition (precuneus). These findings suggest that an imbalance in connectivity of subregions, rather than disturbed connectivity of the RTPJ as a whole, characterizes the connectional disruption of the RTPJ in MDD. This imbalance may account for key symptoms of MDD in cognitive, emotional, and social domains. Hum Brain Mapp 37:2931–2942, 2016 . ©2016 Wiley Periodicals, Inc .